Reconstruction of occupational mercury exposures at a chloralkali plant. Issue 2 (1st February 2001) - Williams, P L; Frumkin, H; Pierce, M L; Manning, C C; Elon, L; Sanders, A G
Abstract : OBJECTIVE: To reconstruct historical workplace exposure to mercury (Hg) from 1956 to 1994 at a large chloralkali factory for use in a current epidemiology study of the factory. METHODS: All job activities of the employees were classified into one of 16 exposure categories, and the dates of changes in the processes were identified. Exposures to Hg for each job category, at each period of the plant's operation, were then reconstructed from several data sources. A job-time period-exposure matrix was created, and the individual exposures of former workers were calculated. Data on exposure to Hg in air were compared with modelled concentrations of Hg in air and data on urinary Hg of the employees. RESULTS: Within an exposure category, concentrations of Hg in air were fairly constant for the first 20 years of the factory's operation, but began to increase in the late 1970s. Employees working in the cell room had the greatest exposures to Hg. The exposure estimates had significant correlations (p<0.001) with the urinary data and were well within the modelled range of concentrations of Hg in air. CONCLUSIONS: The highest exposures occurred from 1987 until the plant closed in early 1994 with some exposure categories having time weighted average exposures to Hg greater than 140 μg/m 3 .